Evaluating the apparent diffusion coefficient in MRI studies as a means of determining paediatric brain tumour stages - N. Domínguez-Pinilla; A. Martínez de Aragón; S. Diéguez Tapias; O. Toldos; J. Hinojosa Bernal; M. Rigal Andrés; L.I. González-Granado (Neurología (English Edition), 2016)
Background: The apparent diffusion coefficient (ADC) in MRI seems to be related to cellularity in brain tumours. Its utility as a tool for distinguishing between histological types and tumour stages remains controversial. Procedures: We retrospectively evaluated children diagnosed with CNS tumours between January 2008 and December 2013. Data collected were age, sex, histological diagnosis, and location of the tumour. We evaluated the ADC and ADC ratio and correlated those values with histological diagnoses. Results: The study included 55 patients with a median age of 6 years. Histological diagnoses were pilocytic astrocytoma (40%), anaplastic ependymoma (16.4%), ganglioglioma (10.9%), glioblastoma (7.3%), medulloblastoma (5.5%), and other (20%). Tumours could also be classified as low-grade (64%) or high-grade (36%). Mean ADC was 1.3 for low-grade tumours and 0.9 for high-grade tumours (P = .004). Mean ADC ratios were 1.5 and 1.2 for low and high-grade tumours respectively (P = .025). There were no significant differences in ADC/ADC ratio between different histological types. Conclusion: ADC and ADC ratio may be useful in imaging-study based differential diagnosis of low and high-grade tumours, but they are not a substitute for an anatomical pathology study. Resumen: Introducción: El coeficiente de difusión aparente (ADC) de la resonancia magnética parece relacionarse con el grado de celularidad de los tumores de sistema nervioso central. Su utilidad para diferenciar el grado tumoral y tipo histológico de los tumores es controvertido. Material y métodos: Estudio retrospectivo de los pacientes pediátricos con diagnóstico de tumor de sistema nervioso central desde enero-2008 a diciembre-2013. Se revisan edad, sexo, localización del tumor y anatomía patológica. Las medidas de ADC y ratio ADC (cociente ADC tumoral/ADC tejido sano) se llevaron a cabo por 2 neurorradiólogos expertos, ciegos al diagnóstico histológico. Se calcula el valor ADC y el ratio ADC y se comparan sus valores con los diagnósticos anatomopatológicos. Resultados: Se incluyen 55 pacientes. La mediana de edad fue 6 años. Los diagnósticos anatomopatológicos fueron: astrocitoma pilocítico (40%), ependimoma anaplásico (16,4%), ganglioglioma (10,9%), glioblastoma (7,3%), meduloblastoma (5,5%), y otros (20%). El 64% fueron de bajo grado (BG) y el 36% de alto grado (AG). La media de ADC fue 1,3 en los de BG y 0,9 en los de AG (p = 0,004). La media de ratio ADC fue de 1,5 y 1,2 (p = 0,025) respectivamente. No hubo diferencias significativas en el ADC/ratio ADC entre los distintos tipos histológicos. Conclusiones: El ADC y ratio ADC son una herramienta útil en la diferenciación por imagen del grado tumoral en los tumores cerebrales pediátricos, sin sustituir a la anatomía patológica. Keywords: Apparent diffusion coefficient, Brain tumours, Children, Magnetic resonance imaging, Palabras clave: Coeficiente de difusión aparente, Tumores cerebrales, Niños, Resonancia magnética